Peran Tarekat Alawiyyah dalam Menghadapi Krisis Spiritual di Kalangan Masyarakat Modern - Fahmi Alaudin (Jurnal Penelitian Ilmu Ushuluddin, 2023)
In this modern era, some humans experience a moral and spiritual crisis. Such as anxiety, restlessness, existential emptiness and distance from God. From these signs, it will result in high levels of stress, frustration, to a decrease in human dignity which will threaten the existence of every human being. So this is where the role of the Alawiyyah congregation is needed as an alternative solution in countering the phenomenon of spiritual crisis among modern society. The purpose of this study is to describe a brief history, teachings and the role of the Alawiyyah Order at the Asy-Syifa Wal Mahmudiyah Islamic Boarding School, Sumedang, West Java. This research is a qualitative descriptive type by practicing library research and field research. Data collection carried out by the author is in the form of interviews, observations and documentation. Data analysis carried out by researchers includes data reduction, data presentation and conclusion drawing. The results of this study indicate that the role of the Alawiyyah tarekat in the Asy-Syifa Wal Mahmudiyah Islamic Boarding School, in facing a spiritual crisis among modern society is to implement several moral values of Sufism including good morals, having a sense of tolerance, peace, gratitude, being kind, and patient. According to K. H. Muhammad Muhyidin Abdul Qadir Al-Manafi, M.A, if all the moral values of Sufism can be implemented in this life, it will produce useful, happy and loving people. In addition, the ethics of society are getting better, so that it gives birth to peace, happiness, and harmony.